2021
DOI: 10.1016/j.jtbi.2021.110739
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical investigation of innate immune responses to lung cancer: The role of macrophages with mixed phenotypes

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…influenced by the half-life of various macrophage phenotypes (43). The abundance of these macrophages indicates the plasticity of TAMs and the potential of targeting TAMs for immunotherapy in medulloblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…influenced by the half-life of various macrophage phenotypes (43). The abundance of these macrophages indicates the plasticity of TAMs and the potential of targeting TAMs for immunotherapy in medulloblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any correlation between M mix and prognosis in this study. A recent research showed that tumor reduction was associated with the percentage of macrophages with mixed M1/M2 phenotypes, and the outcome of these therapeutic strategies targeting TAMs was influenced by the half-life of various macrophage phenotypes ( 43 ). The abundance of these macrophages indicates the plasticity of TAMs and the potential of targeting TAMs for immunotherapy in medulloblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the interaction between macrophages and Treg through ligand receptor interaction may contribute to immunosuppressive status and disease progression (32). Macrophages are the main components of the immune infiltrate of the tumor microenvironment and can produce a variety of phenotypes in different microenvironments, including classically activated (M1) and alternately activated (M2) macrophages (33). M1-like cells are involved in pathogen clearance and proinflammatory responses, and M2-like cells promote tissue remodeling and anti-inflammatory processes and are related to tumor progression (15) that infiltrate tumor tissues, called tumor-associated macrophages, are associated with tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical model has become a powerful, simple and economical tool to quantitatively study the potential mechanism of biological system in recent decades. It is noticed that some literatures have established corresponding mathematical models to describe the dynamical behavior of tumor and macrophages [6,7,8,1,37,9]. R. Eftimie [7] established a three-dimensional mathematical model of tumors, M1 macrophages and M2 macrophages, in which the logistic term describes the self proliferation and recruitment of macrophages.…”
mentioning
confidence: 99%
“…R. Eftimie [7] established a three-dimensional mathematical model of tumors, M1 macrophages and M2 macrophages, in which the logistic term describes the self proliferation and recruitment of macrophages. Raluca Eftimie and Charlotte Barelle [8] took into account the mixed phenotypes macrophages M12 in the tumor microenvironment, and established a four-dimensional mathematical model. Because monocyte input is less and recruitment is ignored, the logistic term in the model only describes the proliferation of macrophages.…”
mentioning
confidence: 99%